KENIZÉ MOURAD AND EARLY MIDDLE EASTERN FEMINISM - Armianu, Irina (The Levantine Review, 2012)
This article explores the waning days of the Ottoman Empire and emergence of the modern state system in the early twentieth century Levant from the purview of Kenizé Mourad's self-narrative Regards from the Dead Princess: Novel of a Life. A work of history and literary fiction, Mourad's novel is an account of the last remnants of a secular Levantine culture, the story of a crumbling empire, and the personal tale of a young woman and her exiled imperial family strewn about the continents, torn between Lebanon, Europe, and the Indian subcontinent.